A Randomized Controlled Trial Comparing the Efficacy of the Delayed Absorbable Polydiaxanone (PDS) Versus Non-Absorbable Polypropylene Sutures for Abdominal Wall Closure Following Midline Laparotomies - Asif, Hamna; Abbassi, Muhammad Hanif; Qureshi, Muhammad Ali Zar; Hamza Afzal, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Abdominal wall closure following midline laparotomy remains a critical factor influencing postoperative morbidity. The choice of suture material plays a crucial role in preventing wound-related complications, such as surgical site infections, dehiscence, and impaired wound healing. Objective: To compare the clinical outcomes of delayed absorbable polydiaxanone (PDS) versus non-absorbable polypropylene sutures for abdominal wall closure in midline laparotomies. Methods: A randomized controlled trial was conducted at Combined Military Hospital, Jhelum, from July 2023 to December 2023. A total of 60 patients undergoing midline laparotomy were randomly assigned to two groups: PDS (n = 30) and polypropylene (n = 30). The primary outcome was wound dehiscence at 30 days post-surgery. Secondary outcomes included surgical site infection (assessed using the Southampton scoring system), postoperative pain (assessed at 7-day and 14-day follow-up), time to wound healing, and duration of hospital stay. Statistical analysis was performed using the chi-square test and the independent t-test, with p < 0.05 considered significant. Results: Wound dehiscence occurred less frequently in the PDS group compared to polypropylene (3.0% vs. 10.0%; p = 0.045). Surgical site infection was significantly lower in the PDS group (p = 0.03), with improved wound healing noted. Postoperative pain scores at 7 and 14 days were significantly reduced in the PDS group (p = 0.02). No significant difference was observed in the length of hospital stay between the two groups. Conclusion: Delayed absorbable polydiaxanone (PDS) sutures demonstrated superior outcomes over non-absorbable polypropylene sutures in terms of reduced wound dehiscence, fewer surgical site infections, faster wound healing, and lower postoperative pain, without affecting hospital stay. These findings suggest PDS as a preferable choice for midline abdominal wall closure.